Role of serum protein electrophoresis in clinically suspected cases of plasma cell dyscrasia: A tertiary care center experience from North India - Kumar, Vijay; Sahu, Priya; Marwah, Sadhna; Nigam, Abhay S (Annals of Pathology and Laboratory Medicine, 2020)
Background: Serum protein electrophoresis (SPE) and its pattern recognition is an excellent screening technique for the detection of paraproteinemias or monoclonal gammopathies. In this study, we assessed SPE patterns in all clinically suspected cases of plasma cell dyscrasia with usual and unusual clinical presentations and correlated with ancillary investigations. Method: We analysed serum protein electrophoresis (SPE) patterns in clinically suspected cases of plasma cell dyscrasia in 2 year duration. Based on SPE pattern these cases were divided into two groups: Group I, with M-component and Group II, without M-component. These cases were reviewed with respect to clinical presentation and correlated with immunofixation electrophoresis and bone marrow aspiration/biopsy findings wherever available, especially in the M band positive cases to differentiate multiple myeloma (MM) from the other conditions. Result: A total of 80 samples were received for SPE, out of these, 56.3% were clinically suspected to have plasma cell dyscrasia. Among these cases 60% were in group I and 40% were in group II. In group II, 39% cases were essentially non neoplastic after relevant investigations. In group I, M-band was observed in 88.9% cases in Î³-region and 11.1% cases in Î²-region. The mean fraction of the M protein was 4.7g/dl with a range of 2.0g/dl to 9.8g/dl. In group II 72.2% showed polyclonal hypergammaglobulinemia, 22.2% showed normal electrophoretic pattern and 5.6% showed hypogammaglobulinemia. Bone marrow aspiration and biopsy were available in 88.9% of all suspected cases. Various haematological neoplasms observed in both the groups, their clinical presentations with interesting facets of the cases have been discussed. Conclusion: Serum protein electrophoresis is one of the most important diagnostic modality in clinical chemistry. It helps to resolve cases with bone marrow plasmacytosis particularly in differentiating between reactive non-neoplastic plasmacytic proliferations from clonal plasma cell disorders. Moreover, it also facilitates the work-up of cases with atypical presentations and thereby paves way to clinch the diagnosis in these ambiguous cases.